كتاب (المُفْرَد وَالمُؤَلَّف) لأبي القاسِم الزّمخْشَرِيّ - دراسةً وتحقيقًا - Shabir | شبير, Ali bin Musa bin Muhammad | علي بن موسى بن محمد (2023)
The book (The Singular and the Author), by Abu al-Qasim al-Zamakhshari (d. 543 AH), a grammatical text, composed in Makkah al-Mukarramah, he made it into two parts, the first for the singular word, and the other for the author from the vocabulary. Under each type, he discussed its sections and conditions. As for the second section, nine types of literature were mentioned: The author is from the verb and the noun, from the letter and the noun, from the letter and the verb, from two letters, from the singular and the author, the author with the author, the singular with the authors, and the author with the authors. I made it in five written copies, and presented it to him with a study in which Al-Zamakhshari dealt with his biography and life. | كتاب (المفرد و المؤلف), لابي القاسم الزمخشري (ت543ه), متن نحوي, الفه بمكة المكرمة, جعله في قسمين, أولهما للمفرد من الكلم, و الاخر للمؤلف من المفردات, ففي قسم المفرد ذكر أنواع الكلم المفرد الثلاثة: الاسم و الفعل و الحرف متناولا تحت كل نوع أقسامه, أحواله, أما القسم الثاني فذكر فيه تسعة ضروب للمؤلفات: المؤلف من الفعل و الاسم, ومن الحرف و الاسم, و من الحرف و الفعل, و من حرفين, و من المفرد و المؤلف, و المؤلف مع المؤلف, و المفرد مع المؤلفين, و المؤلف مع المؤلفين. حققته على خمس نسخ خطية, و قدمت له بدراسة تناولت فيها الزمخشري سيرته و حياته, و بينت في الدراسة منهج الكتاب (المفرد و المؤلف) و مادته, و منهج الزمخشري و مذهبه النحوي فيه.